THEORETICAL AND EXPERIMENTAL STUDY OF INCOMPRESSIBLE FLUID FLOW THROUGH A SLOTTED ORIFICE - Tomaszewska, Barbara (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Prototype designs of orifice flowmeters are commonly used in measurements. One area which has attracted considerable interest includes slotted orifices, where a single central opening is replaced by the use of several slots. This paper reports the results of numerical and experimental research of a prototype design of a slotted orifice plate. The movement of the fluid was described with use of Reynolds equations closed by the k-ε turbulence model. The calculations were performed using ANSYS Fluent software package by consideration of the fluid flow through an orifice plate and slotted orifice with the equal β ratio = 0.5. The results of calculations are compared with the measurements. Good qualitative and quantitative conformity was obtained during the study for the C flow coefficient. It was indicated that the slotted orifice generates a considerable lower pressure drop in comparison to an orifice plate while maintaining comparable level of measurement uncertainty.